2001
DOI: 10.1021/jf011046u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Iron Uptake by Phytic Acid, Tannic Acid, and ZnCl2:  Studies Using an In Vitro Digestion/Caco-2 Cell Model

Abstract: The objective of this study was to document the effects of phytic acid, tannic acid, and zinc on iron uptake in an in vitro digestion/Caco-2 cell culture model. The effects of phytic acid and tannic acid on iron uptake were measured at increasing molar ratios of FeCl3 to phytic acid or tannic acid. Maximal inhibition of iron uptake by phytic acid occurred at a 1:10 ratio of Fe to phytic acid. Dialyzable Fe decreased with a low Fe to phytic acid ratio but increased with Fe:phytic acid ratios greater than 1:3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 17 publications
6
141
2
Order By: Relevance
“…The infant cereal named eight cereals-honey showed phytate × calcium/ zinc molar ratios above the critical value within the range of 150-200, which have been associated with a decrease in zinc bioavailability. It has been reported that removing phytate increases iron bioavailability in the Caco-2 cell in vitro model [24,25] . Since iron solubility, iron retention, transport efficiency, and uptake efficiency percentages can be used as bioavailability predictors [8,26,27] , our results showed that three of the four infant cereals analyzed after phytase treatment increased iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…The infant cereal named eight cereals-honey showed phytate × calcium/ zinc molar ratios above the critical value within the range of 150-200, which have been associated with a decrease in zinc bioavailability. It has been reported that removing phytate increases iron bioavailability in the Caco-2 cell in vitro model [24,25] . Since iron solubility, iron retention, transport efficiency, and uptake efficiency percentages can be used as bioavailability predictors [8,26,27] , our results showed that three of the four infant cereals analyzed after phytase treatment increased iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…In cell culture, a 1:1 ratio of tannic acid to Fe inhibited 92% of Fe absorption (Glahn and Wortley, 2002). When applied in a more complicated feed matrix as part of a meal, this effect was lessened, but still evident (Yun et al, 2004), suggesting that degree of mineral absorption inhibition is influenced by the presence of other nutrients in the feed matrix during digestion.…”
Section: The Interactions Between Minerals and Condensed Tanninsmentioning
confidence: 99%
“…Phenolic compounds have been reported to have high inhibitory effect on iron absorption (Glahn et al 2002) as well as reduction in protein and carbohydrate digestibility (Emine Nur Herken, 2005). Their presence in foods in high quantities is therefore not desirable.…”
Section: Sensory Evaluationmentioning
confidence: 99%